The Harmony of Philosophical Thinking and Artistic Image in the Phenomenology of Creativity - Tilovova Muyassar Yuldosh Kizi (Researchparks Publishing, 2022)
This article discusses the development of the theoretical and methodological foundations of the phenomenological method in Uzbek literature aimed at analyzing the phenomena of the author's and reader's consciousness, a leader in world literature. Because many methods of artistic analysis focus on the structural side of the text. The phenomenological method leads to the phenomenology of the mind, its worldview, personality, imagination, beliefs, yemotions and personality through the text, rejecting all other external factors.